Biomarkers for Presymptomatic Doxorubicin-Induced Cardiotoxicity in Breast Cancer Patients. - Valentina K Todorova; Issam Makhoul; Eric R Siegel; Jeanne Wei; Annjanette Stone; Weleetka Carter; Marjorie L Beggs; Aaron Owen; V Suzanne Klimberg (PLoS ONE, 2016)
Cardiotoxicity of doxorubicin (DOX) remains an important health concern. DOX cardiotoxicity is cumulative-dose-dependent and begins with the first dose of chemotherapy. No biomarker for presymptomatic detection of DOX cardiotoxicity has been validated. Our hypothesis is that peripheral blood cells (PBC) gene expression induced by the early doses of DOX-based chemotherapy could identify potential biomarkers for presymptomatic cardiotoxicity in cancer patients. PBC gene expression of 33 breast cancer patients was conducted before and after the first cycle of DOX-based chemotherapy. Cardiac function was evaluated before the start of chemotherapy and at its completion. Differentially expressed genes (DEG) of patients who developed DOX-associated cardiotoxicity after the completion of chemotherapy were compared with DEG of patients who did not. Ingenuity database was used for functional analysis of DEG. Sixty-sevens DEG (P<0.05) were identified in PBC of patients with DOX-cardiotoxicity. Most of DEG encode proteins secreted by activated neutrophils. The functional analysis of the DEG showed enrichment for immune- and inflammatory response. This is the first study to identify the PBC transcriptome signature associated with a single dose of DOX-based chemotherapy in cancer patients. We have shown that PBC transcriptome signature associated with one dose of DOX chemotherapy in breast cancer can predict later impairment of cardiac function. This finding may be of value in identifying patients at high or low risk for the development of DOX cardiotoxicity during the initial doses of chemotherapy and thus to avoid the accumulating toxic effects from the subsequent doses during treatment.